IMPLEMENTASI SCREENING KESEHATAN (CEK TEKANAN DARAH, KADAR KOLESTEROL, ASAM URAT, GULA DARAH DAN LINGKAR PERUT) UPAYA PENCEGAHAN PENYAKIT TIDAK MENULAR (PTM) PADA KARYAWAN UNIVERSITAS ISLAM AS-SYAFI’IYAH - sukmalara, dini; Fatimah, Siti; Sumarno, Agus; Idris, Muhammad; Pijiharti, Imelda; Agustin, Marini; Meilita, Zuhriya (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat, 2024)
ABSTRACT According to the Ministry of Health in 2016, around 71 percent of the causes of death in the world are non-communicable diseases (NCDs) which kill 36 million people per year. About 80 percent of these deaths occur in middle- and low-income countries. 73% of deaths are currently caused by NCDs, 35% of which are due to heart and blood vessel diseases, 12% by cancer, 6% by chronic respiratory diseases, 6% due to diabetes, and 15% are caused by other NCDs. One preventive measure that can be taken is to carry out early detection and early follow-up of NCDs risk factors. Objective: Increase public health understanding and peace of mind (especially UIA employees) regarding the prevention of NCDs by conducting health screening, early detection of NCDs prevention and monitoring of risk factors for major non-communicable diseases NCDs, including smoking, unhealthy eating patterns, lack of physical activity, obesity, stress, consumption of alcoholic beverages, hypertension, hyperglycemia, hypercholesterolemia, and excess urate levels. The method used is univariate analysis to look at the results of the NCDs screening, the population of UIA employees by taking a sample of the total population. The results of employees suffering from hypertension were 53%, overweight and obese 54%, high cholesterol levels in the blood 64%, suffering from diabetes mellitus 24% and high uric acid levels in the blood 20%. The conclusion is that the high rates of hypertension, overweight and obesity as well as blood cholesterol levels of more than 50% indicate that there is an unhealthy and unhealthy lifestyle among UIA employees. Suggestions are expected from UIA employees to change their lifestyle to be healthier, carry out preventive efforts and further consultation and control with health services for curative efforts in preventing NCDs.